Aspects of gulf surges and tropical upper tropospheric troughs in the North American monsoon - Newman, Andrew James, author; Johnson, Richard, advisor; van den Heever, Sue, committee member; Maloney, Eric, committee member; Bienkiewicz, Bogusz, committee member (Colorado State University. Libraries, 2011)
Gulf surges are transient events that propagate along the Gulf of California (GoC) from south to north, transporting cool moist air toward the deserts of northwest Mexico and the southwest United States during the North American monsoon (NAM). The general features and progression of surge events are well studied but the dynamical characteristics and evolution are still unclear. Tropical upper-tropospheric troughs (TUTTs) are another critical transient event occurring during the NAM that enhance precipitation on their western flank. The mechanism of precipitation enhancement associated with TUTT passage needs further refinement as well. To address these unknowns, a number of convection-permitting simulations are performed over the entire core monsoon region for the 12-14 July 2004 gulf surge and TUTT event that occurred during the North American Monsoon Experiment. This allows for extensive comparison with many observational platforms. A control simulation is able to reproduce the surge event reasonably well, capturing all the important observed features on 12 and 13 July. The dynamical evolution of the surge event notes two distinct features, a precursor event on 12 July and the actual surge on 13 July. Using shallow water theory, the feature on 12 July is likely a coastally trapped, slightly non-linear Kelvin wave. This feature is important because it introduces cooler, moister air into the southern and central GoC. The surge signature develops early on 13 July in the southern GoC and is likely a coastally trapped non-linear Kelvin wave throughout its lifetime. Sensitivity simulations show that the convective outflow is critical to the intensity of the simulated surge, in agreement with past studies. The removal of mountain gap flows into the GoC from the Pacific Ocean along the Baja Peninsula shows they are not critical in surge initiation and evolution; the surge and its general character remain. A unique approach to examine the TUTT precipitation enhancement mechanism is used where the vorticity anomaly associated with the TUTT is removed in the initial conditions. It is shown that the TUTT likely enhances convection along the Sierra Madre Occidental (SMO) through slightly increased shear and slightly more convective available potential energy (CAPE) near the SMO. These slight differences lead to enhanced precipitation and microphysical evolution. The control simulation generates 23% more precipitation during the primary period of TUTT interaction with the SMO and has enhanced graupel, cloud and precipitation ice and supercooled liquid water contents, which is related to changes in lightning production. Finally, two dimensional dry idealized simulations examine some attributes of the observed surge. The GoC LLJ, multiple convective outflows, and slope of the isentropes along the GoC all influence the character of the idealized surge. The slope of the isentropes, which is a consequence of the heat low over the Southwest US, is most important, followed by the convective outflows, and GoC LLJ. The sloped isentropes create a unique thermodynamic environment which significantly impacts gravity wave phenomena like Kelvin waves and bores. Convective outflows modulate surge intensity and its complexity while the GoC LLJ only enhances the surge intensity.
Keywords: gulf surges; monsoon; TUTT; coastally trapped disturbances; North America